Variabilitas Konsumsi Pangan Pada Masyarakat Nusa Tenggara Timur =Food Consumption Variability for East Nusa Tenggara People - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Abstract The analysis intended to identify the various food consumption of the people of East Nusa Tenggara was carried out by using the data from Susenas in East Nusa Tenggara Province in 1996. There were 500 households included in the analysis those were classified according to income level (low, middle, high) and residence (rural, urban). The estimation of the consumption function was using Maximum Likelihood Method (MLE). Results of the analysis revealed that expenditure allocation for foodstuffs was 63% and 37% for non-foodstuffs. High-income people combined rice and corn to meet their carbohydrate needs while low-income people relied on corn. Protein sources including fish and meat were not affordable by the people of East Nusa Tenggara.